Antimicrobial and toxicity tests of flavonoid total Dendrophthoe pentandra (L) miq from false ashoke tree (Polyalthia longifolia) - Aliyah Fahmi; Rumondang Bulan Nasution; Hamonangan Nainggolan (Pascasarjana Universitas Negeri Medan, 2018)
Abstract: Research on antimicrobial and toxicity tests of flavonoid total Dendrophthoe pentandra (L) Miq from false ashoke tree (Polyalthia longifolia) have been done. This study aims to determine the activity of toxicity of total flavonoid of Dendrophthoe pentandra (L) Miq as mistletoe of false ashoke tree (P. longifolia) based on Brine Shrimp Lethality Test (BSLT) method using Artemia salina Leach shrimp larvae obtained Lethal Concentration (LC50) of 30.06 mg / L which means strong toxic activity. Antimicrobial test of flavonoid total has used the diffusion method in order to obtain the inhibit zone diameter on Streptococcus mutans at the total flavonoids concentration of 3%, 6% and 9% were 6; 9 and 17.25 mm, in Escherichia coli is 3.55; 4.25 and 9.15 mm and at Candida albicans is 8.30; 4 and 5.30 mm where S. mutans and E. coli are greater but C. albicans less affect but still have good inhibitory activity so effective to be developed as antimicrobial agents.Keywords:false ashoke leaves, antimicrobial, toxicity, diffusion and BSLT